Low power wake-up receiver and wake-up signal technology in 5G-Advanced - Xueming PAN; Xin QU (Dianxin kexue)
Power consumption is critical for wearable and IoT (Internet of things) devices.Device standby with micro-watt level power consumption can be enabled by using low-power wake-up receiver/wake-up signal technology, which can increase the device battery life and are widely applicable to smart wearables, Internet of things, smart phones, etc.Study item on low power wake-up receiver and wake-up signal technology has been approved in 3GPP, and was considered as one of the iconic technologies for mobile devices in 5G-Advanced.Preliminary discussion on low power wake-up receiver and wake-up signal technology were provided, including use case and requirements, low power wake-up receiver structure, wake-up signal design, mobility and measurement aspects, co-existence with legacy system, anti-interference design.